(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Indiscriminate discharge of industrial effluent has become a serious problem for the agro-ecological environment in most of the areas of Bangladesh. The effects of loom-dye effluents on seed germination and early seedling growth of rice (Oryza sativa L.) were investigated by conducting an experiment in the laboratory of the Department of Agricultural Chemistry of Bangladesh Agricultural University, Mymensingh. Three types of loom-dye effluents were applied in sterilized petridishes at different loading ratios. Seven treatments (i.e., T0, T1, T2, T3, T4, T5 and T6 with 0, 5, 10, 25, 50, 75 and 100% effluent, respectively) of each effluent were used following completely randomized design (CRD) and replicated three times. Subsequently, Pb, Fe, Zn, Mn and Cr accumulation were also investigated in the harvested rice seedlings. Rice seed showed a significant difference in germination percentage with varying levels of effluent application at different days after setting of germination. The decreased seed germination rate and seedling growth of rice were observed with increased concentration of loom-dye effluents. The highest germination speed (97.8%) was obtained from control whereas the lowest germination speeds were obtained from T5 of black, and T6 of both black and violet effluents. Phytotoxic effects of loom-dye effluents on germination and radical length were extreme at 100% effluent concentration having the order of black > violet > pink. The maximum radical length (6.4 cm) and plumule length (7.5 cm) were observed with T1 of pink dye effluent whereas the minimum length of radical and plumule were obtained from T6 treatment of the effluents. The highest fresh weight (39.8 mg petridish–1), dry weight (5.7 mg petridish–1) and seedling vigor index (746.7%) were also observed from T1 of pink dye effluent. The maximum uptake of Pb, Fe, Mn and Zn was 0.48, 3.81, 0.79 and 0.13 μg g−1, respectively. The uptake of Cr was below the detectable limit. Total heavy metal accumulation in rice was in the following order: Fe>Mn>Pb>Zn>Cr. Results showed that the higher concentration of loom-dye effluent showed the higher toxic effects on different parameters of germination and early seedling growth compared with the lower effluent concentrations. J. Bangladesh Agril. Univ. 17(2): 153–160, June 2019